Online Learning for Vocational Education: Uncovering Emerging Themes on Perceptions and Experiences - Amirah Rasyidah Roslin; Bahbibi Rahmatullah; Nor Zuhaidah Mohamed Zain; Sigit Purnama; Qahtan M. Yas (Journal of Vocational Education Studies, 2022)
The worldwide spread of the COVID19 pandemic has shifted the teaching of theory and practical sessions in all schools, including in the field of vocational education, to online learning. Theoretical and practical learning in vocational education become more flexible and is not confined to physical space. A systematic literature review of selected research articles was conducted using Systematic Reviews and Meta-Analyses (PRISMA) guidelines based on important keywords of online learning in vocational education. Initially, the research identified 89 articles from Scopus databases by using a specific keywords search. After the screening phase, ten articles were finalized to meet the criteria for review and discussion in this paper. The thematic analysis conducted reveals several exciting topics discussed in this paper; students' experiences, teaching and learning performances, and the teacher and students' perception of online learning for vocational education. The study implies the cruciality of understanding the role of teachers and students in vocational education so online learning can be optimized and conducted efficiently.